Handbook of research on human capital and people management in the tourism industry - Costa, Vânia Gonçalves, 1978-; Moura, Andreia Antunes, 1983-; Mira, Maria do Rosário, 1963- (Advances in hospitality, tourism, and the services industry book series., 2021)
"This book examines human resource policies for tourism destinations and explores human capital managerial business approaches in tourism"--